2015
DOI: 10.1049/iet-smt.2014.0198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of squirrel cage geometry on the synchronisation of the line start permanent magnet synchronous motor

Abstract: This study deals with the impact of squirrel cage design on the synchronisation of the line start permanent magnet synchronous motor (LSPMSM). The numerical model of the machine is based on the finite element method. Special attention is paid to the analysis of the synchronisation process during the start-up process for high inertia loads. The results for two different designs of squirrel cage are presented and discussed. The strategy for the optimisation of the cage shape of the LSPMSM has been proposed and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…4. The obtained results are analogues to the literature [4], 6]. Maximum load torque t start , which enables LSPMSM to start-up and obtain subsynchronous speed, is given by the formula (1) where: t start -maximum load torque, t r -LSPMSM starting torque, ∆u -voltage drop during motor start-up, t brake -LSPMSM braking torque due to permanent magnets.…”
Section: Starting Properties -Start-upsupporting
confidence: 64%
See 1 more Smart Citation
“…4. The obtained results are analogues to the literature [4], 6]. Maximum load torque t start , which enables LSPMSM to start-up and obtain subsynchronous speed, is given by the formula (1) where: t start -maximum load torque, t r -LSPMSM starting torque, ∆u -voltage drop during motor start-up, t brake -LSPMSM braking torque due to permanent magnets.…”
Section: Starting Properties -Start-upsupporting
confidence: 64%
“…Except load torque, moment of inertia also limits the LSPMSM starting capability. For high value of the load inertia, like fans, LSPMSM can start-up but simultaneously be not able to run in synchronism and stall below synchronous speed [4]. LSPMSM with double squirrel cage rotor construction can withstand this phenomenon and make the motor able to synchronize successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the current density in the rotor bar, δ b , which is about 4-7 A/mm 2 , cross-sectional area of the rotor bar is obtained by Equation (16). End ring current per pole is calculated by Equation (17). After that, the cross-sectional area of the rotor end ring is obtained by Equation (18) corresponding to the current density in the rotor end ring, δ e , which is about 5-8 A/mm 2 .…”
Section: Outer Rotor Designmentioning
confidence: 99%
“…Better performance at the startup and rapid synchronization have been achieved with the low magnetizing inductance [16]. The impact of the structure of the squirrel cage on the motor synchronization showed that the asymmetrical cage is useful to improve the startup performance [17]. Research has been conducted on motor efficiency and production cost by using different magnet materials [18].…”
Section: Introductionmentioning
confidence: 99%
“…The relevant start-up parameters are assessed using the approach described in [4], where the parameters are evaluated based on the value of the synchronizing torque T 80 defined as the asynchronous torque generated by the cage winding at a speed close to the final operating speed 0018-9464 © 2018 IEEE. Personal use is permitted, but republication/redistribution requires IEEE permission.…”
Section: Modeling Strategy and Techniquesmentioning
confidence: 99%